Slit ventricle syndrome: clinical and diagnostic pitfalls - Zapolska, Gabriela; Gościk, Elżbieta; Matuszczak, Ewa; Fedosiewicz-Wasiluk, Małgorzata; Turek, Grzegorz; Dębek, Wojciech; Komarowska, Marta; Hermanowicz, Adam (Pediatria Polska - Polish Journal of Paediatrics, 2018)
Slit ventricle syndrome (SVS) consists of clinical symptoms of intracranial hypertensive syndrome (IHS), which include severe, usually intermittent headaches; vomiting and possibly some degree of decreased consciousness; and impairment in hydrocephalic children with an apparently working ventriculoperitoneal shunt (VPS), without ventricular enlargement on computed tomography (CT) or magnetic resonance imaging (MRI). Signs of IHS include increasing head circumference and papilledema. The syndrome has been typically observed in children with neonatal or infant hydrocephalus, three to six years after VPS implantation. Therapeutic decisions are difficult and often depend only on the clinical presentation of IHS. There is much controversy about the treatment of SVS. Immediate shunt revision may pose a problem in putting the shunt system in the slit ventricles or removing the old shunt, which can be attached to the ependyma.